ICTs in the hospitality industry : an importance-performance analysis among small family-owned hotels - Garbin Praničević, Daniela (Array, 2020)
This study delivers the importance-performance analysis of the information and communication technology (ICT) driven solutions among small and family-owned hotels (SFH) in Croatia. The analysis reflects the opinions of owners of 21 SFH, all of which are members of the National Association of Family and Small Hotels (OMH). The findings demonstrated the existence of a significant gap between the perception of the importance of specific innovations and actual hotel performances. In most cases, hotel performances are rated significantly lower than the perceived importance of particular innovation, which indicate that resources should be better and more wisely allocated. In some cases, hotels do not recognise the benefits of ICTs used or are not satisfied with the results. The primary constraint for higher integration of the ICTs within this sample is the lack of financial resources. The study reveals the importance-performance gaps within the perception of technological innovations in the SFHs, elaborates on potential constraints for more substantial reliance on ICTs and discusses the possible implications. Finally, the study provides recommendations for future research.